Manipulations of perceived economic inequality: a systematic review and meta-analysis - Sánchez Rodríguez, Ángel (2025)
In recent years, there has been an exponential growth of research investigating the psychological consequences of economic inequality. More and more experimental manipulations of economic inequality have been used, allowing researchers to infer the causal effects of inequality on a wide range of psychosocial variables. We conducted a systematic review of research that has manipulated perceived economic inequality, followed by a meta-analysis examining (a) the effectiveness of different perceived economic inequality manipulations and (b) their impact on the different outcomes studied (e.g., descriptive norms). In total, 60 studies were included in the meta-analysis, with an average of 141 participants per group (total of 31,637 participants). The meta-analytic results showed that experimental manipulations affected inequality perceptions, yet there is large variability in their effectiveness. Although the type of paradigm used and characteristics of the manipulations accounted for some of this heterogeneity, much remains unexplained. Moreover, experimental manipulations of perceived economic inequality mostly influenced descriptive norms and perceptions followed, in order, by stereotypes, belief systems, motivations/values, causal attributions, and social/economic comparison. We discuss the implications of our findings and offer advice for researchers using paradigms to manipulate economic inequality.